ANALISIS HUBUNGAN PENGUNGKAPAN TANGGUNGJAWAB SOSIAL PERUSAHAAN DAN KEPEMILIKAN INSTITUSIONAL - Rico Aglesio Ricardo; Haryanto Haryanto (Diponegoro Journal of Accounting, 2017)
This study aims to examine the relationship between the disclosure of corporate social responsibility (CSRD) and institutional ownership. This study used secondary data. The population in this study consisted of all manufacturing companies listed in Indonesia Stock Exchange in 2012 - 2015. The sampling method in this research is purposive sampling, and the number of samples in this study were 61 companies. This study used the technique of multiple linear regression analysis. The empirical results of this study show that CSRD, dimensions employee relations and dimension product has a positive and significant relationship with institutional ownership. While dimension of community and institutional ownership has not had a significant relationship, and the environmental dimension has a negative and significant relationship with institutional ownership.